Pożytki z teatru. Na przykładzie realizacji teatralnych Artura Żmijewskiego i Zorki Wollny - Sawicka, Jadwiga (Wydział Sztuki UR, 2018)
The article discusses using theatre in the practice of visual artists based on the cases of two artists. It presents different goals with which that medium has been used: in the staging of a Catholic Mass in theatre by Artur Żmijewski, and in playing the role of Ophelia by eleven actresses of different ages in a performance directed by Zorka Wollny. Considering the previous work of the two artists, one may say that theatre-related projects have been part of the interests and practice of both of them. They are both interested in working with people, yet the aim of Żmijewski’s experiment was affecting the audience and Wollny’s one – emancipation of the actresses and the text.
The advantages of theatre
Keywords: teatr; sztuka współczesna; zaangażowanie społeczne; aktorki; rytuał; performans; emancypacja; ciało; Artur Żmijewski; Zorka Wollny; theatre; contemporary art; social involvement; actresses; ritual; performance; emancipation; body